Dietary Intake of Benzo(a)pyrene and Risk of Esophageal Cancer in North of Iran - Hakami, R; Mohtadinia, J; Etemadi, A; Kamangar, F; Nemati, M; Pourshams, A; Islami, F; Nasrollahzadeh, D; Saberi-Firoozi, M; Birkett, N (Nutrition and cancer, 2008)
One etiologic factor for high incidence of esophageal squamous cell carcinoma (ESCC) in Golestan (Northeastern Iran) might be exposure to polycyclic aromatic hydrocarbons. We examined whether food and water are major sources of benzo(a)pyrene (BaP) exposure in this population. We used a dietary questionnaire to assess the daily intake of staple food (rice and bread) and water in 3 groups: 40 ESCC Golestan cases, 40 healthy subjects from the same area, and 40 healthy subjects from a low-risk area in Southern Iran. We measured, by high-performance liquid chromatography combined with fluorescence detection, the BaP concentration of bread, rice, and water in samples obtained from these 3 groups and calculated the daily intake of BaP. Mean BaP concentration of staple foods and water was similar and within standard levels in both areas, but the daily intake of BaP was higher in controls from the high-risk area than in controls from the low-risk area (91.4 vs. 70.6 ng/day, P < 0.01). In the multivariate regression analysis, having ESCC had no independent effect on BaP, whereas residence in the low-risk area was associated with a significant decrease in total BaP intake. Polycyclic aromatic hydrocarbons might, along with other risk factors, contribute to the high risk of ESCC in Golestan.